2022
DOI: 10.3389/fimmu.2022.935800
|View full text |Cite
|
Sign up to set email alerts
|

SRSF1 acts as an IFN-I-regulated cellular dependency factor decisively affecting HIV-1 post-integration steps

Abstract: Efficient HIV-1 replication depends on balanced levels of host cell components including cellular splicing factors as the family of serine/arginine-rich splicing factors (SRSF, 1–10). Type I interferons (IFN-I) play a crucial role in the innate immunity against HIV-1 by inducing the expression of IFN-stimulated genes (ISGs) including potent host restriction factors. The less well known IFN-repressed genes (IRepGs) might additionally affect viral replication by downregulating host dependency factors that are es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 177 publications
(259 reference statements)
0
11
0
Order By: Relevance
“…For internal control, the RNA Process Control Kit (Roche, Cat# 07099622001) was used as instructed by the manufacturer. As previously described [25] glyceraldehyde-3-phosphate dehydrogenase (GAPDH) mRNA was used as an additional housekeeping gene.…”
Section: Methodsmentioning
confidence: 99%
“…For internal control, the RNA Process Control Kit (Roche, Cat# 07099622001) was used as instructed by the manufacturer. As previously described [25] glyceraldehyde-3-phosphate dehydrogenase (GAPDH) mRNA was used as an additional housekeeping gene.…”
Section: Methodsmentioning
confidence: 99%
“…Silencing, both at the transcriptional and epigenetic levels, is another antiviral mechanism that HIV-1 can override with the help of Vpr. SRSF1, an IFN-modulated splicing factor, was observed to hinder overall LTR activity in Jurkat and THP-1 cells [ 126 ]. In this context, a recent pioneering study involving direct RNA nanopore sequencing in CD4 + T cells identified the Vpr-mediated upregulation of ciTRAN, an HIV-modulating circular RNA that sequesters SRSF1 to prevent it from burdening viral gene expression [ 127 ].…”
Section: Signaling Disruption and Immune Evasionmentioning
confidence: 99%
“…In the following sections, we describe the characteristics and functional hallmarks of these two protein families and discuss their impact on viral replication but focus on two representatives, which have recently been shown to be significantly modulated by interferons [ 46 , 47 ]. SRSF1 will be examined as the main representative of the SRSF family, and hnRNPA0 will be discussed as a representative of the hnRNP family, both selected due to their significant downregulation in gene expression upon interferon stimulation among all the examined RBPs ( Table 1 ).…”
Section: Hiv-1 Depends On Interactions With Host Cell Splicing Factorsmentioning
confidence: 99%
“…SRSF1 is also a key regulator in the gene expression and RNA processing of HIV-1 [ 78 , 79 , 93 ]. The overexpression of SRSF1 has been shown to suppress viral transcription, while the knockdown increases the total viral mRNA levels [ 46 , 94 , 95 , 96 ]. As mentioned above, several HIV-1 pre-mRNA SREs are bound by SRSF1, which enhances the recruitment of the core spliceosomal components [ 92 ].…”
Section: Hiv-1 Depends On Interactions With Host Cell Splicing Factorsmentioning
confidence: 99%